Persuasive Through Ethos, Logos, and Pathos in BTS' Speech at The White House - Nabila Putri, Renita; Muharman, Deddy; Mashuri, Fath (Yayasan Ilomata, 2024)
Race is the diversity given by God Almighty. Race can be understood as the distinctive characteristics of a nation in groups based on different physical characteristics. This difference is a beautiful thing because humans do not only consist of one group, but also various groups with differences that can complement one another. Unfortunately, in the reality of social life, there is still discrimination against certain races with different physical forms from the majority in a region. The United States is an example of a country that has the highest level of racism in the world. The Asian-American race often experiences acts of racism that result in fatalities. BTS, a band from South Korea, became the representative of Asians invited by Joe Biden to speech at The White House to express their concern about hate crimes. The purpose of this study is to analyze BTS' speech regarding racial issues towards Asians at The White House from the perspective of Rhetorical theory using the elements of ethos, logos, and pathos. The speech reflected the reality of racism towards Asian ethnic groups, as well as a solution to end this problem by fighting racism at all levels of society. This research uses the interview method by collecting primary and secondary data from relevant books, journal articles, and websites to analyze the Rhetoric speech by BTS in order to get accurate results. The implications of the results of this study include improving Rhetoric not only used in Political occasions but can be used for anyone like BTS did from an entertainment background.